Analyzing the Impact of Family Dynamics on Juvenile Delinquency among Senior High School Students - Daria, Shiela Andria T.; Dela Cruz, Ana Marie V.; Samson, Edilyn M.; Sevilla, Marielle L.; Mobo, Froilan D.; Villa, Elizabeth B. (Future Science / FSH-PH Publications, 2025)
This study investigated the link between family dynamics and juve-nile delinquency among Filipino senior high school students. Intact families were associated with greater emotional stability and less delinquency than single-parent or adoptive families; however, strong parental support and communication mitigated negative out-comes in non-traditional families. Family conflict significantly pre-dicted negative outcomes (stress, instability, academic struggles, delinquency). High parental involvement, especially in academics, was associated with positive outcomes. These findings highlight the importance of supportive family environments and underscore the need for family-focused interventions and policies to prevent juve-nile delinquency.